PENERAPAN SISTEM PENILAIAN SASARAN KERJA PEGAWAI (SKP) DALAM RANGKA PENINGKATAN KINERJA PEGAWAI NEGERI SIPIL (PNS)DI BALAI PELESTARIAN NILAI BUDAYA JAWA BARAT - Hartanto, Shanti (Universitas Madura, 2016)
This research is based on PP No. 46 Tahun 2011 that regulate appraisal performance of civil servants. This regulation is recently implemented at the Institute for Balai Pelestarian Nilai Budaya (BPNB) Jawa Barat at the end of 2014. Performance appraisal system with SKP is different from the previous assessment system which was using DP3. In this new system, employees actively involved in determining the plan SKP within a year. To implement SKP, BPNB need to organize massive socialization and facilitate field personnel with the expert. Through four dimensions of John Miner which are include quality, quantity, usage hours of work and cooperation, the researcher tried to explain how the performance appraisal system based on SKP. This study use qualitative methods and the phenomenological approach, a technique of determining informants purposefully in BPNB Jawa Barat employees with office data processing cultural values and positions of researcher. The result of this research show that the performance appraisal system in BPNB Jawa Barat received a positive response such as benefits for employees and more objective performance appraisal system compared to the previous one. However, the SKP system is still in a period of adjustment so researcher found some obstacles in its implementation which are not all employees BPNB Jawa Barat mastered the technology of e-SKP, lack of human resources to handle SKP, less support of internet facilities, lack of rigor in the determination of the charging and collection deadline, and duty office for research and data processor of cultural values in the e-SKP less in line with their duties in the field.